INNOVATIVE WORK BEHAVIOR: EFEK KNOWLEDGE SHARING - Wahyu Rindyani; Anwar Mansyur (Jurnal GeoEkonomi, 2024)
The research conducted aims to determine the effect of knowledge sharing on innovative work behavior in the workplace. This research method uses descriptive quantitative method. The sample technique in this study used a saturated sample method totaling 95 people who were none other than employees of PT Phapros, Tbk. Data collection techniques used in this study through questionnaires. Data analysis using SPSS software through the stages of validity test, reliability test, hypothesis testing. Based on the results of data analysis, knowledge donation and knowledge collection are two dimensions of knowledge sharing that affect innovative work behavior.